دور القضاء الإداري في حماية عناصر النظام الايكولوجي - بريبش, رضا (جامعة الوادي University of Eloued, 2017)
تضع قوانين حماية البيئة التزاما محددا وفق معايير قانونية وتقنية يتعين على الأشخاص مراعاتها لحماية المحيط الحيوي، وتحدد هذه القوانين مستخدمي هذه الموارد الطبيعية والمنتفعين من هذه الالتزامات، وهم الأجيال الحالية والمقبلة، ومنذ تكريس مبدأ التنمية المستدامة تحول هذا الالتزام من أخلاقي إلى قانوني، وخلق قاعدة تنص على أنه من سبب أضرارا للبيئة يعتبر مسؤولا عن هذه الأضرار، أخذت هذه القاعدة طابع إداري، وبرز معها مسألة ضبط وسائل وكيفيات وإجراءات المساءلة الإدارية وأساليب تعويض هذه الأضرار، وثار التساؤل حول قدرة القواعد المتعارف عليها وفق المسؤولية الإدارية في حماية وإصلاح الأضرار الايكولوجية، وبالتحديد القضاء الإداري، أم أن هذا النوع من الحماية بحاجة إلى نظام خاص ينسجم مع خصوصيات الضرر الايكولوجي وضمان حقوق ضحاياه؟ Abstract: The environmental protection laws put an obligation specified in accordance with legal and technical standards, individuals need to take it into consideration for the protection of the vital environment. These rules identify users of the natural resources and their commitments, they represent actual and future generations. Since devoting sustainable development’s principle, these commitments had shifted to be legal instead of moral, and has created a key rule stating that ‘the causative of the environment damages is considered legally responsible for it’ this rule took an administrative aspect and arises along with it issues such as means, modalities and procedures for administrative accountability and methods of compensation for such damages. The question emerged also about the ability of common rules to protect and repair the ecological damage “the administrative court” or this type of protection needs a special system in line with the ecological damage’s degree and guarantee of victims rights?
Keywords: القضاء الاداري؛ النظام الايكولوجي؛ حماية النظام؛ التناسب؛ التنوع الايكولوجي؛ دعوى الالغاء؛ دعوى التعويض